Mechanisms for high spin in black-hole neutron-star binaries and kilonova emission: inheritance and accretion. Issue 1 (12th December 2022) - Steinle, Nathan; Gompertz, Benjamin P; Nicholl, Matt
ABSTRACT: A black-hole neutron-star binary merger can lead to an electromagnetic counterpart called a kilonova if the neutron star is disrupted prior to merger. The observability of a kilonova depends on the amount of neutron star ejecta, which is sensitive to the aligned component of the black hole spin. We explore the dependence of the ejected mass on two main mechanisms that provide high black hole spin in isolated stellar binaries. When the black hole inherits a high spin from a Wolf–Rayet star that was born with least 10 per cent of its breakup spin under weak stellar core-envelope coupling, relevant for all formation pathways, the median of the ejected mass is ≳10 −2 M⊙ . Though only possible for certain formation pathways, similar ejected mass results when the black hole accretes 20 per cent of its companion's envelope to gain a high spin. Together, these signatures suggest that a population analysis of black-hole neutron-star binary mergers with observed kilonovae may help distinguish between mechanisms for spin and possible formation pathways. We show that these kilonovae will be difficult to detect with current capabilities, but that future facilities, such as the Vera Rubin Observatory, can do so even if the aligned dimensionless spin of the black hole is as low as ∼0.2. Our model predicts kilonovae as bright as Mi ∼ −14.5 for an aligned black hole spin of ∼0.9 and mass ratio Q = 3.6.